The Use of Polymer Admixtures for Concrete Quality 45 Mpa Using the Combination of Bangkalan and Pandan Aggregate - Dewi Pertiwi; Theresia MCA; Ahmad Wahyu Setiawan (Journal of Civil Engineering, Planning and Design, 2022)
Madura Island has natural resource potential, one of which is the result of mining excavations, including class C. Bangkalan Regency has aggregates that could be used in concrete mixtures, including fine aggregate (sand) and coarse aggregate (gravel). The compressive strength of concrete using Bangkalan aggregate, on the other hand, is just 20 MPa, or the regular concrete category. High-quality concrete is one of the most frequently utilized building materials nowadays. Admixture is required to build high-strength concrete, particularly in Bangkalan Regency. In this research, a polymer admixture was used.The goal of this study was to determine the proportion of polymer additives used in the concrete mixture when fine aggregate from Lumajang, coarse aggregate 10/20 from Bangkalan, and coarse aggregate 5/10 from Pandaan were used to achieve a concrete compressive strength of 45 MPa.Based on the findings of research on the usage of polymer-type additives in concrete mixtures using fine aggregate from Lumajang, 10/20 coarse aggregate from Bangkalan, and 5/10 coarse aggregate from Pandaan, a concrete compressive strength of 0.95% Fc '45 Mpa was obtained from cement weight. At the design concrete quality of Fc '45 Mpa, the average compressive strength of concrete aged 28 days is 45.54 Mpa.